Responses of 10-year-old cacao trees (Theobroma cacao L.) to thinning, fertilizer and climatic conditions - Moses, Dennis D. (1979)
Tesis (Mag.Sc.) -- CATIE, Turrialba (Costa Rica) -- UCR, San José (Costa Rica), 1979